A Phenomenological Study on International Doctoral Students’ Acculturation Experiences at a U.S. University - Campbell, Throy A. (Journal of International Students, 2015)
A phenomenological method was used to analyze ten international doctoral students’ description of their lived experiences at a United States (U.S.) university. The analysis was based on the theoretical premise of how students acculturate to their new educational settings. Three broad overlapping themes emerged: (1) participants’ past experiences that influenced their desire to study in the U.S.; (2) participants’ interactions within academic and non-academic settings; and (3) the role of family relationships during their studies within the U.S. The study revealed that the students: were optimistic about the societal opportunities from studying in the U.S., were appreciative of their interaction with instructors, had inadequate relationship with supervising professors, participated in limited social activity outside of academic settings, and made adjustment to family relationships.